Keberlanjutan Industri Gula Kelapa Kecamatan Bagelen Sebagai Upaya Pengembangan Ekonomi Lokal - Anik Setyowati; Prihadi Nugroho (Jurusan Perencanaan Wilayah dan Kota, 2016)
Local economic development is one of the instruments to actualize regional development utilizing their local resources. Resource utilization in a region also depends on the potential in the region, such as the coconut sugar industry in the Bagelen District, Purworejo that use raw materials and local labors. Although coconut sugar industry is small-scale industries and households, but its existence began ogled by the international market. The high demand can not be met by the owner of the industry due to lack of manpower and the middlemen involved in marketing. Because of it, fears about the sustainability of the coconut sugar industry in the District Bagelen. This research used mixed method with Triangulation Design models. The results showed that coconut sugar and crystal sugar are difficult to continue to be a growing industry as the local economic development efforts. Coconut sugar faced a problem with the unstable price, while crystal sugar doesn’t have permission to label products, so they rely on the existence of the companies